Pioneering Studies on Cephalopod's Eye and Vision at the Stazione Zoologica Anton Dohrn (1883-1977) - Dröscher, Ariane (Frontiers in Physiology, 2016)
From the late nineteenth century onwards, the phenomena of vision and the anatomy and physiology of the eye of marine animals induced many zoologists, ethologists, physiologists, anatomists, biochemists, and ophthalmologists to travel to the Zoological Station in Naples. Initially, their preferred research objects were fish, but it soon became evident that cephalopods have features which make them particularly suited to research. After the first studies, which outlined the anatomical structure of cephalopods' eyes and optic nerves, the research rapidly shifted to the electrophysiology and biochemistry of vision. In the twentieth century these results were integrated with behavioral tests and training techniques. Between 1909 and 1913 also the well-known debate on color vision between ophthalmologist Carl von Hess and zoologist Karl von Frisch took place in Naples. Largely unknown is that the debate also concerned cephalopods. A comparative historical analysis of these studies shows how different experimental devices, theoretical frameworks, and personal factors gave rise to two diametrically opposing views.